Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter R - Review of Basic Concepts - Chapter R Test Prep - Review Exercises - Page 84: 111



Work Step by Step

RECALL: $(a+b)(a^2-ab+b^2) = a^3+b^3$ Note that: $\sqrt[3]{2^2} = (\sqrt[3]{2})^2$ $16=4^2$ Thus, if we let $a=\sqrt[3]{2}$ and $b=4$ The expression above becomes: $=(a+b)(a^2-ba+b^2)$ which is equivalent to $(a+b)(a^2-ab+b^2)$ Therefore, using the formula in the recall part above, the given expression simplifies to: $=(\sqrt[3]{2})^3+4^3 \\=2+64 \\=\color{blue}{66}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.